Popular sim, ingênuo jamais!: disputa por significação na Bienal Naïfs do Brasil - Moniche, Bianca Júlia da Silva (Universidade Federal de São Carlos, 2023)
In this work, I propose to analyze and understand disputes over meaning about Naive Art in Brazil, focusing on possible debates about the formation of a national identity and its overlapping with racial themes from the Naïve Biennials of Brazil, cultural event organized by SESC - Piracicaba since 1992. In other words, I seek to answer what Naive Brazil is, what representations and narratives are produced about and in Naïve Art regarding the conception of national identity. To do this, I established two specific objectives that will conduct this investigation: I-Understand how socially the constitution of the naïve category, as a social and II-Understand the possible relationships between the naive category and a national identity and the possible articulations such as the racial debate. Here I adopt the content analysis methodology, applied from the perspectives of Cultural and Postcolonial Studies.
Popular yes, never naive!: dispute for significance at the Brazilian Naïfs Biennial
Keywords: Arte naïf; Arte popular; Identidade nacional; Cultura popular; Estudos culturais; Naïf art; Popular art; National identity; Cultural studies; Popular culture; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS